2022
DOI: 10.3389/fcimb.2022.999627
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics reveals specific host metabolism-microbiome associations in intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is the most devastating subtype of stroke, but effective prevention and treatment strategies are lacking. Recently, gut microbiome and its metabolitesis are considered to be an influencing factor of stroke. However, little is known about the effects of the gut microbiome on ICH and host metabolic activity. Therefore, we used 16S sequencing, macrogenomics sequencing and untargeted metabolomics to explore the differences in gut microbial-metabolome interactions between patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Over the last few decades, rapid advances in microbiome and metabolome studies have greatly aided our understanding of the pathogenic mechanisms underlying ICH ( Zhang et al, 2021b ; Chen et al, 2022 ). Most studies are animal or case–control studies, which can demonstrate an association with ICH but cannot establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last few decades, rapid advances in microbiome and metabolome studies have greatly aided our understanding of the pathogenic mechanisms underlying ICH ( Zhang et al, 2021b ; Chen et al, 2022 ). Most studies are animal or case–control studies, which can demonstrate an association with ICH but cannot establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-omics research revealed a significant decrease in the phylum of Firmicutes and a significant increase in Bacteroidetes in ICH patients. At the genus level, Streptococcus, Lactobacillus, Bifidobacterium, and Akkermansia were found to be abundant in ICH patients ( Chen et al, 2022 ). Moreover, Li et al (2022b) and Xiong et al (2022) reported that the abundance of Akkermansia in patients with parenchymal hemorrhage was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed that octanoylcarnitine was negatively associated with OC. To date, the expression of octanoylcarnitine in different tumors remain conclusive [ 33 ], the expression in OC needs to be further verified. We also found that another acylcarnitine metabolite ( cis-4-decenyl carnitine ) was negatively correlated with OC.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Tan et al (2021), with a cohort of 40 acute ischaemic patients and 92 controls, showed that the intestinal microbiota was different in stroke patients compared with healthy controls, especially those with increased stroke severity, in which SCFA levels, especially acetate, were associated with an increased risk of 90-day poor functional outcomes. A recent clinical study also demonstrated that gut dysbiosis takes place after haemorrhagic stroke (Chen, Wang, et al, 2022): By using 16S RNA sequencing, macrogenomics sequencing and untargeted metabolomics to explore the differences in gut microbial-metabolome interactions between patients with intracerebral haemorrhage and healthy control populations, they found a significant decrease in the phylum of Firmicutes and a significant increase of Bacteroidetes in haemorrhagic stroke patients, which is accompanied by changes in serum microbial metabolites and correlates with the severity of intracerebral haemorrhage (Chen, Wang, et al, 2022). In addition, a role of GM in post-stroke prognosis and early stroke outcome has been demonstrated in a study including 104 patients with acute ischaemic stroke and 90 healthy individual showing that the stroke dysbiosis index (SDI) correlated not only with brain injury but also with early unfavourable outcome (Xia et al, 2019).…”
Section: Stroke Alters Gm Compositionmentioning
confidence: 96%